Association between food-related media content and the eating behaviors of Korean adults according to household type - Yun, Ahyoung; Jung, Hyein; Kim, Byungmi; Choi, Yoonjoo (Frontiers in Nutrition, 2025)
BackgroundSociocultural changes and the proliferation of digital platforms have led to the increasing popularity of food-related content in Korea, including Mukbang, Cookbang, and Sulbang. Despite concerns that such content may influence eating habits, research focusing on adults is limited. Therefore, this study examined the association between media content and eating behaviors, stratified by household type, while considering the living environment.MethodsData were derived from an online survey conducted by the National Cancer Center, comprising responses from 1,270 participants divided in a 1:1 ratio based on whether they watched food-related content. The participants reported their eating behaviors and viewing habits. Multivariable logistic regression was employed to identify relationships after adjusting for sociodemographic variables, with analyses stratified by household type.ResultsThe analysis results showed that in multi-person households, viewing all content types were significantly associated with late-night eating and delivery/take-out meal consumption, with some also related to the frequency of dining out. Conversely, in single-person households, significantly positive associations were exclusively found between Mukbang viewing and late-night eating as well as delivery/take-out meal consumption; Cookbang and Sulbang did not yield statistically significant results. In stratified analysis, more subgroups exhibited associations with eating behaviors, regardless of content type among multi-person households.ConclusionThe findings suggest that viewing food-related content is linked to dietary behaviors, with effects varying depending on household type. Furthermore, acknowledging the impact of such content on eating behaviors to explore means of utilizing it positively to foster healthy eating habits is imperative.